Novel structure twin lamella - HU SHANLIANG; ZHU HUA; DENG YANMING; ZHOU DONGMEI; WANG ZHEN; CHEN SHUIQIN; DU WEN (2016)
The utility model belongs to the technical field of the crystal element, especially, relate to a novel structure twin lamella. It has solved short class of technical problem of prior art life. This novel structure twin lamella includes the base plate, is equipped with the potsherd respectively on the base plate two sides, is equipped with first conducting layer between every potsherd and the base plate, and the length of two potsherds equals just length weak point in the length of base plate of potsherd is equipped with respectively on the wherein one end two sides of base plate that the piece is strengthened to the cantilever type and two cantilever types strengthen forming the cell body between the piece. The utility model discloses the advantage lies in: reduce the amplitude of fluctuation, further strengthened structural strength and long service life.